Computer diagnostics for the analysis of table tennis matches - Yu, L. J.; Zhang, H.; Hu, J. J (International Journal of Sports Science and Engineering, 2008)
With the development of computer science and technology, the analysis of techniques and tactics of ball games is developing in three dimensions. First, the visualization technology is being employed in game analysis. Secondly, modern scientific computations are increasingly used in the diagnostic analysis. Thirdly, with more and more researches conducted in game analysis, people are beginning to be aware of the many factors which are likely to influence the performance of the players in ball games.